Utilization of Tannin Containing Shrub Legumes for Small Ruminant Production in Indonesia - Wina, Elizabeth (Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Shrub legumes have been well established in Indonesia and some of which contain significant levels of tannin. Several methods of tannin analysis have been conducted and correlated with its biological property of tannin. Total phenolics and total tannin measured by Folin Ciocalteau have a high correlation with the biological assay of tannin using gas in vitro method. Tannin values measured by the above methods negatively correlated with protein digestibility. Several feeding experiments on tannin containing shrub legumes using Calliandra calothyrsus as a model plant have been conducted. Feeding in fresh condition or silage form is the best way of feeding tannin containing forages. Several methods were tested to deactivate tannin include PEG addition, soaking in water or alkaline solution. Starch addition is one of the alternatives to mask the effect of tannin as it improved the performance of sheep fed tannin-containing legumes. Cofeeding with other leguminous leaves is another technique to utilize tannin in shrub legumes as protein binding agent. Several experiments showed that tannin could reduce the worm burden in ruminant although its utilization as anthelminthic agent in Indonesia is still limited. In conclusion, tannin containing shrub legumes have several beneficial effects to improve small ruminant production. Key words: Tannin, legumes, protein binding, anthelmintic agent, small ruminant